SWOT analysis and Encapsulation of Apple Business Model (International Journal of Food and Nutritional Sciences, 2019)
Apple Computer, Inc. is a Public Limited Company. It was founded on 1st April,1976. It wasfounded by Steve Jobs, Steve Wozniak and Ronald Wayne. It serves worldwide with retailstores. Its Headquarters is at Apple Park Way, Cupertino, California, U.SIt relates toconsumer Electronics, Software and Online services Industry. In this Paper an attempt ismade to analyze the strengths, Weaknesses, Opportunities and Threatsof Apple ComputerInc. An attempt is also made to analyze Customer Segments, Value Proposition, Channels,Customer Relationships, Revenue Streams, Cost Strutureof Apple Computer Inc